Armenia : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper reviews economic developments in the Republic of Armenia during the 1990s. Real GDP declined by a cumulative 60 percent in 1992-93; price changes reached hyperinflation levels in late 1993; and real wages declined by nearly 50 percent in the course of that year. In the fall of 1994, the authorities formulated a comprehensive program of stabilization and structural reform that was supported in December 1994 by a first purchase under the Systemic Transformation Facility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet